Reflecting and Adapting Informed Consent to fit within an Islamic Moral Landscape and in Muslim Contexts - Padela, Aasim (Studia Bioethica, 2019)
In this commentary I consider how the bioethical construct of informed consent maps onto an Islamic moral universe. I will describe how homeomorphic equivalents of informed consent theory can be found within the Islamic tradition in order to argue that Islamic morality demands structures similar to those of informed consent. After this theoretical exposition, I will identify several features of Muslim culture that need to be accounted for when adapting “western” consent procedures for use in Muslim contexts. Such a “translation” would result in informed consent procedures that may look and feel different than those in European and American contexts, but nonetheless are ethically robust and achieve similar ends.